Fatigue performance of bonded crack retarders in the presence of cold worked holes and interference-fit fasteners. (December 2017) - Syed, Abdul Khadar; Zhang, Xiang; Moffatt, James E.; Maziarz, Robert; Castelletti, Luigi; Fitzpatrick, Michael E.
Highlights: GLARE straps provided significant improvement to fatigue crack growth life. Curing residual stress has little effect on cold work induced residual stress field. Cold expansion delayed crack remerging from the fastener hole. Abstract: Bonded crack retarders (BCR) are of particular interest in the aerospace applications for improving fatigue performance of airframe structural assemblies. In respect of structural integrity, a reinforcing strap will require additional fixing by means of riveting or bolting to ensure fail-safety. Cold expansion is currently the common practice of increasing the fatigue performance of fastener holes. Thermal residual stresses introduced during the adhesive curing process at 120 °C for strap bonding are of potential concern as they may affect the cold expansion stresses and thereby the fatigue crack growth performance of the fastener hole and reinforced structural assembly. In this paper, Single-Edge-Notched Tension (SENT) specimens are made of aluminium alloy 2624-T351. Fibre metal laminate GLARE is used as BCR strap. SENT specimens with BCR and with BCR plus an interference fit fastener are used to investigate the fatigue crack growth performance. Residual stress was measured by neutron diffraction method on specimens with BCR plus fastener. It is found that the GLARE strap provides a 2.3 × improvement in life comparing to a plain specimen, and a 1.75 × life improvement when a fastener is installed in a cold expanded hole.